2016
DOI: 10.7554/elife.14199
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations of MeCP2 in glutamatergic neurons highlight their contributions to Rett and other neurological disorders

Abstract: Many postnatal onset neurological disorders such as autism spectrum disorders (ASDs) and intellectual disability are thought to arise largely from disruption of excitatory/inhibitory homeostasis. Although mouse models of Rett syndrome (RTT), a postnatal neurological disorder caused by loss-of-function mutations in MECP2, display impaired excitatory neurotransmission, the RTT phenotype can be largely reproduced in mice simply by removing MeCP2 from inhibitory GABAergic neurons. To determine what role excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 54 publications
6
82
0
Order By: Relevance
“…Consistent with rapid aging and neurodegeneration, increased expression of KSRP also resulted in a decrease in axonal outgrowth via downregulation of the growth factor GAP-43’s mRNA (Bird et al, 2013). Decreasing expression of MeCP2 in glutamatergic neurons of mice led to a shorter lifespan and various neurological abnormalities (Meng et al, 2016). All in all, regulation at the level of miRNA synthesis could have dire consequences on the lifespan of cells.…”
Section: Mirna Synthesis/actionmentioning
confidence: 99%
“…Consistent with rapid aging and neurodegeneration, increased expression of KSRP also resulted in a decrease in axonal outgrowth via downregulation of the growth factor GAP-43’s mRNA (Bird et al, 2013). Decreasing expression of MeCP2 in glutamatergic neurons of mice led to a shorter lifespan and various neurological abnormalities (Meng et al, 2016). All in all, regulation at the level of miRNA synthesis could have dire consequences on the lifespan of cells.…”
Section: Mirna Synthesis/actionmentioning
confidence: 99%
“…Recent evidence has shown that MeCP2 R306C mutation prevents it from interacting with the NCoR/histone deacetylase 3 (HDAC3) complex, which causes impairments in social and cognitive functioning [18]. In the developing brain stem, this impairment will more than likely have downstream effects such as perturbations in excitatory [19] and inhibitory [20] pathways, which in turn will have knock-on effects on vital brain regions implicated in sympathetic and parasympathetic elements of the autonomic nervous system (ANS). Any imbalance will result in dysautonomia; however whilst, autonomic manifestations in RTT include anxiety, pupillary dilation [21], raised serotonin receptor binding in brain stem nuclei [22], low vagal tone with poor vagal response to hyperventilation [23], lower heart rate variability with prolonged QTcF [15] and uncontrolled albeit normal sympathetic tone due to minimal negative feedback of the parasympathetic system [24], due to the inherent heterogeneous plasticity of RTT particularly in terms of maturity-related brainstem functioning [25], these manifestations are more than likely to differ between individuals and so the precise trajectory in terms of the developmental progression of dysautonomia in RTT is at the moment unclear.…”
Section: Introductionmentioning
confidence: 99%
“…32 In contrast, deletion from glutamatergic cells causes anxiety and tremor. 40 Interestingly, postnatal deletion of Mecp2, even within a mature nervous system, results in RTT-like phenotypes. 41,42 In contrast, activation of a previously silenced Mecp2 allele globally, or within GABAergic neurons, reverses many established RTT-like phenotypes including locomotor, behavioural and aberrant functional and structural synaptic plasticity (see Fig 1).…”
Section: Mecp2 Is Essential For Normal Brain Functionmentioning
confidence: 99%